2016
DOI: 10.1093/toxsci/kfw042
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Behavioral Impairments Evoked by Low-Level Exposure to Tobacco Smoke Components: Comparison with Nicotine Alone

Abstract: Active maternal smoking has adverse effects on neurobehavioral development of the offspring, with nicotine (Nic) providing much of the underlying causative mechanism. To determine whether the lower exposures caused by second-hand smoke are deleterious, we administered tobacco smoke extract (TSE) to pregnant rats starting preconception and continued through the second postnatal week, corresponding to all 3 trimesters of fetal brain development. Dosing was adjusted to produce maternal plasma Nic concentrations e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 36 publications
(30 reference statements)
5
42
0
4
Order By: Relevance
“…We found that low TSE levels, comparable to secondhand smoke exposure (i.e. producing plasma nicotine levels one-tenth of those in typical smokers), nevertheless engendered synaptic dysfunction in acetylcholine (ACh) and serotonin (5-hydroxytryptamine, 5HT) systems, culminating in impaired cognitive and emotional behaviors (Hall et al, 2016;Slotkin et al, 2015). TSE exposure had greater effects than did comparable treatment with nicotine alone and indeed, TSE was similar to a 10-fold higher nicotine level; that is, TSE simulating secondhand exposure elicited outcomes like nicotine at active smoking levels.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…We found that low TSE levels, comparable to secondhand smoke exposure (i.e. producing plasma nicotine levels one-tenth of those in typical smokers), nevertheless engendered synaptic dysfunction in acetylcholine (ACh) and serotonin (5-hydroxytryptamine, 5HT) systems, culminating in impaired cognitive and emotional behaviors (Hall et al, 2016;Slotkin et al, 2015). TSE exposure had greater effects than did comparable treatment with nicotine alone and indeed, TSE was similar to a 10-fold higher nicotine level; that is, TSE simulating secondhand exposure elicited outcomes like nicotine at active smoking levels.…”
mentioning
confidence: 91%
“…Recently, we developed a tobacco smoke administration model in pregnant rats that ensures reliable dosing and avoids the stress of inhalation exposure (Hall et al, 2016;Slotkin et al, 2015). We paralleled the standard technique for nicotine delivery in pregnant rats, namely subcutaneously-implanted pumps (Slotkin, 2008) that deliver standardized tobacco smoke extract (TSE).…”
mentioning
confidence: 99%
“…С курением во время беременности связаны проблемы в обуче-нии, поведении, общих когнитивных функциях, а так-же изменения, касающиеся функционирования слу-ховой зоны мозга у детей [41, 82,123], вследствие воздействия никотина повышается риск развития множественных пороков развития у плода [104]. Пассивное курение, как низкодозовое воздействие никотина, также приводит к нейроповеденческим, когнитивным нарушениям и увеличению риска ре-спираторного дистресс-синдрома у новорожденных [33, 69,82,212].…”
Section: пренатальные эффекты никотина на эмбриональное развитие и отunclassified
“…Точно так же Shacka et al [160] предположили, что централь-ный контроль моторной функции у самцов может быть более уязвимым для пренатального никотина, так как пренатально леченные самцы на 14-й день гестации не показывали гиперактивности после стимуляции никотином. Действие никотина во вре-мя беременности значительно нарушает структуры субпопуляций нейронов ДА в ВТО и другие структу-ры мезолимбической системы, что может вызвать тяжелые эффекты на нейронных сетях, вовлеченных в процессы привыкания и подкрепления, целена-правленного поведения и спонтанной и вызванной гиперреактивности у молодых крыс [67,82,99].…”
Section: воздействие никотина связано с поломunclassified
See 1 more Smart Citation